P104 One year failure rates for de novo ventriculo-peritonealshunts in under 3- month-old children. Issue 3 (14th February 2019) - Bentley, E; Ved, R; Amato-Watkins, A; Lang, J; Zilani, G; Bhatti, I; Leach, P
Abstract : Objectives: Historically VPS failure and infection rates are higher for neonates than for older children. We compared our one year VPS failure and infection rates in under 3-month-olds with those of older children. Design: A retrospective, single centre study comparing 1 year survival and infection rates of VPS in under 3-month-olds verses older children. Subjects: 58 children under 3 months of age underwent VPS insertion between January 2007 and December 2016. Methods: Data was collected by three independent reviewers from electronic files and case notes. Data was analysed using descriptive statistics and one year shunt survival curves were produced. Results: For children under 3 months there was a 29.3% one-year shunt failure rate, of which 2 were shunt infections (3.4%). In patients greater than 3 months, the shunt malfunction rate was 23.4% and the infection rate was 4.3%. There were no shunt-related mortalities in either group. Conclusions: Children under 3-months-old undergoing VPS insertion should not automatically expect an increased 1 year failure or infection rate compared with older children. Reasons for this may be increased sub-specialisation, improved neonatal care and use of antibiotic impregnated catheters.